Ophiostomatalean Fungi (Ascomycota, Ophiostomatales) Associated with Three Beetles from Pinus sylvestris var. mongolica in Heilongjiang, China - Zheng Wang; Caixia Liu; Yingjie Tie; Xiuyue Song; Huimin Wang; Quan Lu (Journal of Fungi)
Globally, forest decline and tree mortality are rising due to climate change. As one of the important afforestation trees in northeast China, Pinus sylvestris var. mongolica is suffering from forest decline and the accompanying pests. Certain fungi from the ophiostomatalean contribute to forest pest outbreaks and can be pathogenic to pine trees. However, only a limited number of ophiostomatalean fungi associated with beetles infesting Pinus sylvestris var. mongolica have been identified. In this study, 293 ophiostomatalean fungi were isolated from Acanthocinus griseus, Ips chinensis, and Pissodes nitidus infesting Pinus sylvestris var. mongolica in Heilongjiang Province, including Graphilbum griseum sp. nov., Gra. nitidum sp. nov., Graphilbum sp., and Ophiostoma ips. Ophiostoma ips was the dominant species, followed by Graphilbum sp., Graphilbum griseum, and Gra. nitidum, which accounted for 73.38, 17.41, 7.17, and 2.05% of the isolated ophiostomatalean fungi, respectively. Fungi associated with different beetles are diverse, even within the same host. This study deepens our understanding of the pest-associated fungi of P. sylvestris var. mongolica and provides a basis for exploring the causes of forest decline.